Cleaved high-molecular-weight kininogen inhibits neointima formation following vascular injury - Daniel, Jan-Marcus; Reich, Fabian; Dutzmann, Jochen; Weisheit, Simona; Teske, Rebecca; Gündüz, Dursun; Bauersachs, Johann; Preissner, Klaus T.; Sedding, Daniel G. (Thrombosis and Haemostasis, 2015)
Cleaved high-molecular-weight kininogen (HKa) or its peptide domain 5 (D5) alone exert anti-adhesive properties in vitro related to impeding integrin-mediated cellular interactions. However, the anti-adhesive effects of HKa in vivo remain elusive. In this study, we investigated the effects of HKa on leukocyte recruitment and neointima formation following wire-induced injury of the femoral artery in C57BL/6 mice. Local application of HKa significantly reduced the accumulation of monocytes and also reduced neointimal lesion size 14 days after injury. Moreover, C57BL/6 mice transplanted with bone marrow from transgenic mice expressing enhanced green fluorescence protein (eGFP) showed a significantly reduced accumulation of eGFP+-cells at the arterial injury site and decreased neointimal lesion size after local application of HKa or the polypeptide D5 alone. A differentiation of accumulating eGFP+-cells into highly specific smooth muscle cells (SMC) was not detected in any group. In contrast, application of HKa significantly reduced the proliferation of locally derived neointimal cells. In vitro, HKa and D5 potently inhibited the adhesion of SMC to vitronectin, thus impairing their proliferation, migration, and survival rates. In conclusion, application of HKa or D5 decreases the inflammatory response to vascular injury and exerts direct effects on SMC by impeding the binding of integrins to extracellular matrix components. Therefore, HKa and D5 may hold promise as novel therapeutic substances to prevent neointima formation.
Keywords: Cleaved high-molecular-weight kininogen (HKa); cell adhesion; inflammation; smooth muscle cells; neointimal formation